The Prevalence of Vertical Transmission of HIV Infection in Maharat Nakorn Ratchasima Hospital - Thitinant Samutchaikij; Pisake Tongsawatwong (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To determine the prevalence of vertical transmission of HIV infection in Maharat Nakorn Ratchasima Hospital.Design: Retrospective, descriptive study.Materials and Methods: This retrospective, descriptive study had recruited 205 pregnant women with HIV infection and delivery in Maharat Nakorn Ratchasima Hospital between October 1, 2005 and September 30, 2008. Thirty nine of them were excluded because of no antenatal care and no antiretroviral therapy. The diagnosis of vertical transmission was identified by positive of PCR for HIV-DNA in children. Twenty six patients were then excluded due to loss follow up and 4 of them have stillbirths or neonatal death. They did not have a laboratory examination. There were 136 children who came for follow-up. Data were extracted from medical records and reviewed. Results: The overall vertical transmission rate was 4.41% (6/136). According to mode of delivery, 3.96% (4 cases) was normal delivery, 14.29% (1 case) was delivered by vacuum extraction and 5.26% (1 case) by emergency cesarean delivery. However, gestational age and premature rupture of membranes had not effected on vertical transmission. Conclusion: The prevalence of vertical transmission of HIV infection in Maharat Nakorn Ratchasima Hospital was 4.41%. Elective cesarean delivery did not prevent maternal-to-fetal transmission.